POWER REQUIREMENT ANALYSIS FOR THE SURABAYA INTELLIGENCE TRANSPORT SYSTEM BUILDING (SITS) - Huda, Nurul; Suhariyanto (Universitas Muhammadiyah Surabaya, 2024)
Surabaya is the capital city of East Java province, which has a large area of ± 335.28 km², with a population of 2,972,801 (2022). Surabaya as a big city has public street lighting (PSL) from 2017 to 2023 amounting to 557,512 points. To facilitate the monitoring of PSL throughout the Surabaya area, the Surabaya Transportation Agency Government plans to build a PSL monitoring room which will be allocated in the Surabaya Intelligent Transport System (SITS) building which is located on the 2nd floor close to the ATCS monitoring room so that it is centralised. In achieving the plan, it is necessary to analyse the power requirements of the SITS building before and after the addition of PSL monitoring room by comparing the capacity of the existing generator. SITS building power before the addition of PSL monitoring room is 47.366 kW, while the power requirement after the addition of PSL monitoring room is 58.609 kW. Generator power of 110 kW is greater so it does not require additional generator capacity. Keywords: PSL, Traffic Light, SITS